2015
DOI: 10.1007/s11010-015-2435-x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand specific variation in cardiac response to stimulation of peroxisome proliferator-activated receptor-alpha in spontaneously hypertensive rat

Abstract: Left ventricular hypertrophy (LVH) is an independent risk factor for cardiac failure. Reduction of LVH has beneficial effects on the heart. LVH is associated with shift in energy substrate preference from fatty acid to glucose, mediated by down regulation of peroxisome proliferator-activated receptor-alpha (PPAR-α). As long-term dependence on glucose can promote adverse cardiac remodeling, it was hypothesized that, prevention of metabolic shift by averting down regulation of PPAR-α can reduce cardiac remodelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Previous studies demonstrated that abnormalities in cardiac lipid metabolism and energy production is a consistent feature of heart failure [30, 35]. Crucially, the progression of heart failure with pressure overload is associated with decreased PPARα and PPARβ/δ, and reactivation of PPARα, or PPARβ/δ, is sufficient to reverse myocardial dysfunction and hypertrophy, respectively [5, 7, 8, 10]. In the present study, we found myocardial dysfunction was ameliorated by baicalin treatment in TAC hearts, accompanied by reduced myocardial fibrosis, apoptosis signals, and profound restoration of PPARα and PPARβ/δ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that abnormalities in cardiac lipid metabolism and energy production is a consistent feature of heart failure [30, 35]. Crucially, the progression of heart failure with pressure overload is associated with decreased PPARα and PPARβ/δ, and reactivation of PPARα, or PPARβ/δ, is sufficient to reverse myocardial dysfunction and hypertrophy, respectively [5, 7, 8, 10]. In the present study, we found myocardial dysfunction was ameliorated by baicalin treatment in TAC hearts, accompanied by reduced myocardial fibrosis, apoptosis signals, and profound restoration of PPARα and PPARβ/δ.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that baicalin attenuated cardiac hypertrophy in response to hypertrophic stimuli, accompanied by restoration of PPARα and PPARβ/δ. Previously, reactivation of PPARα with different ligands exhibited opposite effects on left ventricular hypertrophy in spontaneously hypertensive rat [7]. However, the protective effects of cardiac PPARβ/δ restoration on cardiac hypertrophy were clearly demonstrated in vitro and in vivo [10, 12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cardiac PPARα expression was unchanged in a model of abdominal aortic banding [38], revealing that the regulation of cardiomyocyte hypertrophy is strongly reliant on the stress source. In hypertensive rats treated with the PPARα agonist medium-chain triglyceride tricaprylin, PPARα activation reduced cardiac oxidative stress without affecting blood pressure [140]. More recently, Harvey and colleagues showed that phenylephrine-induced hypertrophy in H9c2 cardiomyocytes reduces PPARα expression while increasing NOX2 expression and activity [141].…”
Section: Pparαmentioning
confidence: 99%
“…MCAD regulates the first step in the reaction of fatty acid β-oxidation, namely conversion of acyl-coenzyme A into trans -enoyl-CoA [ 36 ]. The synthesis of MCPT1 and MCAD is regulated by nuclear factor PPARα the activation of which promotes the expression of downstream genes, namely, the MCPT1 and MCAD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%